An Investigation of Health and Safety Issues at Highway Construction Sites in Developing Countries - Shah, R. K.; Alqarni, M. (Journal of Advanced College of Engineering and Management, 2018)
Construction activities on highway projects are the key source of safety risks to workers and motorists. Workplace fatalities and  injuries  have  significantly  reduced  since  1970  after  implementation  of  OSHA  (Occupational  Safety  and  Health Administration) regulations. However, ergonomic injuries caused by ergonomic risk factors such as awkward or sustained posture, forceful exertion or stain, contract pressure, exposure to vibration, extreme heat or cold environment  have major impact on the productivity and safety on the highway construction sites. The paper focuses on identifying the existing safety practices  that  aid  to  prevent  ergonomic  injuries  at  the  highway  construction  sites. A  comprehensive  review  of  literature reveals that majority of work place injuries and fatality victims are from private employment whereas a very few injuries coming from the state or local government employees from contractors. The primary data was collected using questionnaire survey, interview and observations and the spreadsheet was used to analyse the collected data about the causes of workplace injuries  and  possible measures. The  survey  results  reveal  that  the most  of  the  injuries  such  as musculoskeletal  disorders, strain  and  accidents  transpired  due  to  the  collision with  equipment  and  vehicle!s  related  incidents. Dump  truck,  tippers, motor graders and cars cause the frequently reported workplace injuries. The paper concludes that use of Personal Protective Equipment (PPE), compliance to safety regulations, improving traffic control system and changing the culture of employers and employees are possible safety practices need to be adopted to mitigate the ergonomic workplace injuries in the highway construction projects particularly in the developing and least developed countries.